Born to be Tough: Traditional Masculinity Ideology and Help-Seeking Attitude in Chinese-Indonesian Men - Chandra, Rachel Theophilia; Himawan, Karel Karsten, Dr. (Psychological Research on Urban Society, 2025)
Despite growing mental health literacy, a gender gap remains in accessing professional assistance, with men often hesitating to seek assistance despite exhibiting poor mental health indicators. This quantitative study investigates the contribution of traditional masculinity ideology to professional help-seeking attitudes among Chinese–Indonesian men using hierarchical regression analysis. Data were collected from 115 Chinese–Indonesian men aged 18–25 years (M = 21.757; SD = 2.050) using the Masculine Role Norms Inventory-Short Form (MRNI-SF) and Attitudes toward Seeking Professional Psychological Help-Short Form (ATSPPH-SF). Results revealed that traditional masculinity ideology significantly predicts (11.4%) professional help-seeking attitudes among young Chinese–Indonesian men. This study suggests the adoption of a culturally sensitive and inclusive approach to masculinity to mitigate the stigma surrounding professional help-seeking among Chinese–Indonesian youth.